2021
DOI: 10.1002/anr3.12137
|View full text |Cite
|
Sign up to set email alerts
|

Pneumorrhachis following cervical spine surgery

Abstract: A 66-year-old man experienced symptomatic pneumorrhachis (air within the spinal canal) following a cervical laminoplasty for the excision of meningioma. Following an uneventful intraoperative course, he suffered a fluctuating hemiparesis of varying severity. Urgent imaging demonstrated extradural and intradural air in the spinal canal. Treatment with supplemental oxygen and dexamethasone was commenced, and the patient's symptoms improved over a period of three days with full resolution at six weeks. Pneumorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Another crucial factor to access when dealing with a pneumorrhachis is the location of the entrapped air, as the clinical consequences of epidural pneumorrhachia and subarachnoid pneumorrhachis are different from each other. According to a previous case report, the rst is innocuous and self-limiting, while the second can be complicated by tension pneumocephalus and meningitis [2,8,12].…”
Section: Discussionmentioning
confidence: 98%
“…Another crucial factor to access when dealing with a pneumorrhachis is the location of the entrapped air, as the clinical consequences of epidural pneumorrhachia and subarachnoid pneumorrhachis are different from each other. According to a previous case report, the rst is innocuous and self-limiting, while the second can be complicated by tension pneumocephalus and meningitis [2,8,12].…”
Section: Discussionmentioning
confidence: 98%
“…Further, another study reported that the occurrence of a delayed presentation of both pneumorrhachis and pneumocephalus due to the presence of CSF leak [11]. Finally, Bautista et al, 2021 reported the occurrence of a pneumorrhachis after a cervical spinal surgery procedure [12]. Although, the speci c cause of the air in ux into the canal are no very well stablished, the leading hypothesis is that it could occur after small dural injuries unperceived during the spinal procedure [12].…”
Section: Discussionmentioning
confidence: 99%
“…When presented with a symptomatic case of pneumorrhachis, the team must try to identify the possible causing agent, to remove it, or treat it with antibiotics, allied with hydration, bed-rest and correct positioning to avoid headaches and couching [12]. Another crucial factor to access when dealing with a pneumorrhachis is the location of the entrapped air, as the clinical consequences of epidural pneumorrhachia and subarachnoid pneumorrhachis are different from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation